Intervening Consumer Behavior on the Importance of Influence Digital Marketing-Product Upgrading and Virality Towards Sustainability of MSMEs in the Society 5.0 Era - Samas Adimisa Mishbah Habibie; Ribut Santosa; Noer Aida Triandini (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2025)
This study examines how digital marketing, product enhancement, and virality affect the sustainability of MSMEs, with consumer behavior as an intervening factor. The research employed statistical methods on a sample of 160 MSMEs from the East Java MSME population. Data analysis was conducted using path analysis techniques, preceded by classical assumption tests. The findings indicate a significant direct impact of digital marketing, product enhancement, and virality on consumer behavior and MSMEs’ sustainability. Additionally, consumer behavior was found to have a significant direct influence on the sustainability of MSMEs. Furthermore, the research reveals a significant indirect effect of digital marketing, product enhancement, and virality on the sustainability of MSMEs through the mediation of consumer behavior. The conclusion obtained means that digital marketing, product upgrading and virality have an influence on consumer behavior. These four things influence the sustainability of MSMEs.